The Relationship between Physical Activity Patterns and Dietary Patterns with Overweight Incidence in Adolescents Age 13-15 Years at Purwajaya Junior High School - Maulidia Dwi; Satriani Satriani; Jamil Anshory (Universitas Pendidikan Indonesia, 2022)
Nutritional problems are a problem that still cannot be fully addressed in every country. One of the nutritional problems that cannot be completely overcome is the problem of overweight. Several factors cause overweight are physical activity and diet. This study aims to determine the relationship between physical activity and diet with the incidence of overweight in adolescents aged 13-15 years at Purwajaya Junior High School. This research is a descriptive correlational study with a cross sectional approach. The population in this study was 93 students consisting of students in grades VII A and VII B. The sample size in this study was 48 students who were taken by purposive sampling. The respondent's eating patterns were obtained by interview using a 24-hour food recall and a food frequency questionnaire (FFQ). The respondent's physical activity pattern was obtained by interview using the IPAQ (International Physical Activity Questionnaire). The results of this study indicate a significant relationship between diet and the incidence of overweight with a p value of 0.002 and a correlation coefficient of 0.336. It also shows a significant relationship between physical activity and the incidence of overweight with a p value of 0.000 and a correlation coefficient of -0.554. The conclusion in this study is that there is a significant relationship between physical activity patterns and eating patterns with the incidence of overweight in adolescents aged 13-15 years at Purwajaya Junior High School.